Elaeagnus angustifolia Plant Extract Induces Apoptosis via P53 and Signal Transducer and Activator of Transcription 3 Signaling Pathways in Triple-Negative Breast Cancer Cells - Fouzat, Arij; Hussein, Ola Jihad; Gupta, Ishita; Al-Farsi, Halema F.; Khalil, Ashraf; Al Moustafa, Ala-Eddin (Frontiers in Nutrition, 2022)
Elaeagnus Angustifolia (EA) is used as alternative medicine in the Middle East to manage numerous human diseases. We recently reported that EA flower extract inhibits cell proliferation and invasion of human oral and HER2-positive breast cancer cells. Nevertheless, the outcome of EA extract on triple-negative breast cancer (TNBC) cells has not been explored yet. We herein investigate the effect of the aqueous EA extract (100 and 200 µl/ml) on two TNBC cell lines (MDA-MB-231 and MDA-MB-436) for 48 hours and explore its underlying molecular pathways. Our data revealed that EA extract suppresses cell proliferation by approximately 50% and alters the cell-cycle progression of these two cancer cell lines. Additionally, EA extract induces cell apoptosis by 40-50%, accompanied by the upregulation of pro-apoptotic markers (Bax and cleaved caspase-8) and downregulation of the anti-apoptotic marker, Bcl-2. Moreover, EA extract inhibits colony formation compared to their matched control. More significantly, the molecular pathway analysis of EA-treated cells revealed that EA extract enhances p53 expression while inhibiting the expression of total and phosphorylated STAT3 in both cell lines, suggesting p53 and STAT3 are the main key players behind the biological events provoked by the extract in TNBC cells. Our findings implicate that EA flower extract may possess an important potential as an anticancer drug against TNBC.